Atmospheric Plasma-Assisted Preparation of Graphene Oxide from Biomass: Characterization and Elemental Analysis - Handayani, A. H.; Amalia, F.; Noviantana, E. V.; Mulyaningsih, T. R.; Waris, A.; Dimyati, A. (National Research and Innovation Agency, 2025)
Graphene oxide (GO) was successfully synthesized using the atmospheric plasma process with biomass precursors, including coconut fronds, palm fronds, and rambutan stems, within a five-minute processing time. Plasma technology converts near-waste materials into valuable resources with potential for various applications. Graphene oxide, in particular, exhibits high mechanical strength, excellent electrical conductivity, good biocompatibility, and a large surface area, making it a highly versatile material. Raman spectroscopy was used to analyze the formation of synthesized graphene. The presence of organic and inorganic elements in graphene oxide was characterized using a scanning electron microscope equipped with energy-dispersive X-ray spectroscopy (SEM-EDS) and neutron activation analysis (NAA). SEM-EDS analysis revealed that the C:O ratio in plasma-derived graphene oxide exceeded 80 % in each sample. NAA identified 22 inorganic elements, which are naturally present in biomass. Understanding the elemental composition of plasma-synthesized graphene oxide is essential for evaluating its potential applications and identifying necessary purification steps. The oxygen content in the synthesized material, which primarily originates from the inherent properties of biomass, can be regulated by optimizing plasma parameters. Using biomass precursors makes plasma-synthesized graphene oxide an economically viable option for large-scale production.